THE DYNAMICS OF TERRA ROSSA SOILS - Atkinson , Dr. Kenneth (مجلة كلية الاداب, 1969)
The recent analysis by Buru (1968) of red soils developed from limestone in El-Marj Plain, Cyrenaica, represents a timely and impressive attempt to study one of the most difficult and unsatisfactorily-understood soil formations in the sphere of pedo logy. As Buru (1968) emphasises, attempts by pedologists to describe the origins, properties, and agricultural capabilities of Red Limestone Soils are shrouded in controversy. In the past, differing interpretations have been placed on the significance of the various properties of Red Limestone Soils. The present paper reviews some of the more tenable theories for the formation of a red solum from limestone parent rock, and discusses some of the important diagnostic profile features which have to be noted and analysed. The material for this discussion is derived from the author's own fieldwork and observations in Jordan and in Turkey, and also from many interesting discussions with Dr. Buru on the properties of red soils in Cyrenaica. The author would like, at the outset, to acknowledge the stimulus and interest which Dr. Buru's work has provided.